The Effect of Zirconia in Hydroxyapatite on Staphylococcus epidermidis Growth - Widowati Siswomihardjo; Siti Sunarintyas; Alva Edy Tontowi (International Journal of Biomaterials)
Synthetic hydroxyapatite (HA) has been widely used and developed as the material for bone substitute in medical applications. The addition of zirconia is needed to improve the strength of hydroxyapatite as the bone substitute. One of the drawbacks in the use of biomedical materials is the occurrence of biomaterial-centred infections. The recent method of limiting the presence of microorganism on biomaterials is by providing biomaterial-bound metal-containing compositions. In this case, S. epidermidis is the most common infectious organism in biomedical-centred infection. Objective. This study was designed to evaluate the effect of zirconia concentrations in hydroxyapatite on the growth of S. epidermidis. Methods and Materials. The subjects of this study were twenty hydroxyapatite discs, divided into four groups in which one was the control and the other three were the treatment groups. Zirconia powder with the concentrations of 20%, 30%, and 40% was added into the three different treatment groups. Scanning electron microscope analysis was performed according to the hydroxyapatite and hydroxyapatite-zirconia specimens. All discs were immersed into S. epidermidis culture for 24 hours and later on they were soaked into a medium of PBS. The cultured medium was spread on mannitol salt agar. After incubation for 24 hours at 37∘C , the number of colonies was measured with colony counter. Data obtained were analyzed using the ANOVA followed by the pairwise comparison. Result. The statistical analysis showed that different concentrations of zirconia powder significantly influenced the number of S. epidermidis colony (𝑃<0.05) . Conclusion. The addition of zirconia into hydroxyapatite affected the growth of S. epidermidis. Hydroxyapatite with 20% zirconia proved to be an effective concentration to inhibit the growth of S. epidermidis colony.